Pengaruh Gaya Kepemimpinan, Beban Kerja, dan Lingkungan Kerja terhadap Work Life Balance PT Bina Bangun Perkasa Kediri - Chindyana Wahyu Bintari; Brahma Wahyu K; Erwin Syahputra (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study is motivated by the importance of balancing work and personal life (work life balance) to enhance employee performance and well-being. The research aims to analyze the influence of leadership style, workload, and work environment on the work life balance of employees at PT Bina Bangun Perkasa Kediri. A quantitative approach was applied using purposive sampling, with all 35 permanent employees selected as respondents. Data were collected through observation, interviews, and questionnaires, and analyzed using classical assumption tests and multiple linear regression. The findings reveal that leadership style and work environment significantly affect work life balance, while workload has no significant effect. Simultaneously, the three variables show a significant effect on work life balance. These results provide theoretical implications regarding the crucial role of leadership and workplace conditions in supporting employees’ work life balance, as well as practical implications for company management to foster a healthy work environment and effective leadership to improve employee well-being